The Quality of Sustainability Reporting in Indonesia: Government, Employee, Competitor, and Customer Perspectives - Ramadhan, Muhammad Adzan; Emrinaldi Nur DP; Rezi Abdurrahman; Lubis, Armensyah (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/Main Objectives: This research examines the influence of government engagement, employee engagement, competitor engagement, and customer engagement on the quality of sustainability reports for energy and basic materials companies listed on the IDX for the 2019-2022 period. Background Problems: Based on the rankings in ASSRAT from 2018-2020, public company participation in disclosing sustainability reports still needs to be higher, and from the ranking results, many companies declined from 2018 to 2022. Novelty: In previous studies, most research was conducted on the disclosure of sustainability reports, but this research focuses on the quality of sustainability reports in Indonesia. Research Methods: The population in this research is energy and basic materials companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique in this research used a purposive sampling technique, and a sample of 30 companies was obtained. The data analysis method used is logistic regression analysis. Finding/Results: The results of this research show that government engagement and customer engagement influence the quality of sustainability reports, while competitors' engagement and employee engagement have no influence on the quality of sustainability reports. Conclusion: Based on the test results, government engagement and customer engagement have an influence on the quality of sustainability reports. Therefore, the increasing government engagement and customer engagement that companies have will certainly improve company the quality of sustainability reports.